The impact of respiratory viruses on lung health after preterm birth - Townsi, N.; Laing, I.; Hall, Graham; Simpson, S. (2018)
Children born preterm, less than 37 weeks' gestation, are at increased risk of viral respiratory infections and associated complications both during their initial birth hospitalisation and in their first years following discharge. This increased burden of viral respiratory infections is likely to have long term implications for lung health and function in individuals born preterm, particularly those with bronchopulmonary dysplasia. Several hypotheses have been put forward to explain the association between early life viral respiratory infection and development of suboptimal lung health and function later in life following preterm birth. Although preterm infants with diminished lung function, particularly small airways, might be particularly susceptible to asthma and wheezing disorders following viral infection, there is evidence that respiratory viruses can activate number of inflammatory and airway re-modelling pathways. Therefore, the aim of this review is to highlight the perinatal and early life risk factors that may contribute to increased susceptibility to viral respiratory infections among preterm infants during early life and to understand how respiratory viral infection may influence the development of abnormal lung health and function later in life.